ANALISIS PERBANDINGAN KURIKULUM PENDIDIKAN INDONESIA DAN JEPANG DALAM MEMBENTUK KARAKTER PESERTA DIDIK - Najiyah, ibtihal (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2026)
Education plays a crucial role in shaping students’ character as preparation for facing increasingly complex global challenges. The differences in curriculum approaches between Indonesia and Japan are important to examine, as both countries emphasize character education as an essential component of their educational systems. This study aims to analyze the comparison of educational curricula in Indonesia and Japan in developing students’ character. The method used is a bibliometric approach by analyzing relevant scientific publications through mapping research trends, keywords, and study focuses. The results show that Indonesia emphasizes character education through specific subjects, while Japan integrates character values into all learning activities and school culture. Japan applies a student-centered approach with collaborative and experiential learning, whereas Indonesia still shows a tendency toward academically oriented instruction. These differences influence the effectiveness of character development in both countries. In conclusion, the success of character education is strongly determined by the consistency of curriculum implementation and the integration of values into daily learning practices.